2018
DOI: 10.1002/anie.201712469
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanozymes: Enzymatic Properties, Catalytic Mechanism, and Applications

Abstract: Nanozymes have advantages over natural enzymes, such as facile production on large scale, long storage time, low costs, and high stability in harsh environments. Carbon nanomaterials (CNMs), including fullerenes, carbon nanotubes, graphene, carbon quantum dots, and graphene quantum dots, have become a star family in materials science. As a new class of nanozymes, the catalytic activity of CNMs and their hybrids has been extensively reported. In this Minireview, recent progress of CNMs based artificial enzymes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
249
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(261 citation statements)
references
References 176 publications
(838 reference statements)
1
249
0
Order By: Relevance
“…OH . Graphene quantum dots (GQDs), as zero‐dimensional derivatives of GMs, have similar peroxidase‐mimicking properties and consequently are used to induce the antibacterial activity of H 2 O 2 at low concentrations . It was revealed that ‐C=O groups are the catalytically active sites and O=C−O‐ groups are the substrate‐binding sites of GQDs, whereas the ‐C−OH groups can inhibit the antibacterial activity of the materials …”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
“…OH . Graphene quantum dots (GQDs), as zero‐dimensional derivatives of GMs, have similar peroxidase‐mimicking properties and consequently are used to induce the antibacterial activity of H 2 O 2 at low concentrations . It was revealed that ‐C=O groups are the catalytically active sites and O=C−O‐ groups are the substrate‐binding sites of GQDs, whereas the ‐C−OH groups can inhibit the antibacterial activity of the materials …”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
“…The atomistic-level exploration of the original active sites of nanozymes is mainly performed by simplifying the singlecomponent catalysts of noble metal nanoparticles [8][9][10], transition metal oxides [11], and carbon-based materials [12,13]. The cascade reactions catalyzed by multiple enzymes in an organism provide great impetus for preparing composite catalysts by integrating different kinds of nanozymes to mimic the complexity of biocatalysis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the electron states of Pt could be significantly modulated by alloying with Fe. [27] Therefore,we used PtFea lloy NRs, [28] having less platinum than monometallic platinum but an improved activity for H 2 Figure 1a and the Supporting Information, Figure S1-a,b). Thel attice fringes with as pacing of 0.250 nm and 0.201 nm could be observed and ascribed to the (311) planes [29] of Fe 3 O 4 NPs and (111) planes of PtFeNRs,respectively,indicated by scanning transmission electron microscopy (STEM;F igure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Nanozymes are enzyme mimics with both the unique properties of nanomaterials and catalytic activities of natural enzymes.Inrecent years,they have been rapidly developed in biosensing, [1][2][3] antibacterial applications, [4,5] and immunoas-says [6] owing to their high stability,l ow cost, and easy preparation. [7,8] In particular, they have shown great promise in reactive oxygen species (ROS)-mediated tumor therapy.…”
Section: Introductionmentioning
confidence: 99%